The prognostic effect of brain natriuretic peptide levels on outcomes of hospitalized patients with COVID-19 - Yazan Abdeen (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Natriuretic peptides are biomarkers of myocardial stress and are frequently elevated among patients with severe respiratory illnesses, typically in the absence of elevated cardiac-filling pressures or clinical heart failure. Elevation of brain natriuretic peptide (BNP) or NT-proBNP is associated with worse outcomes among patients with Acute Respiratory Distress Syndrome (ARDS). We conducted a retrospective cohort study based on a comprehensive review of Electronic Medical Records (EMRs) of patients with Coronavirus Disease 2019 (COVID-19) to evaluate whether BNP on admission has prognostic value on mortality and hospital length of stay (LOS) among patients admitted with confirmed COVID-19 along with the inclusion of additional prognostic variables. Overall, 146 patients were included after analyzing 230 patients’ EMR and excluding potential confounding factors for abnormal BNP. Our statistical analysis did not show a statistically significant association between BNP level and mortality rate (P = 0.722) or ICU LOS ( P = 0.741). A remarkable secondary outcome to our study was that impaired renal function (GFR<60) on admission was significantly associated with an increased mortality rate (P = 0.026) and an increased ICU LOS (P = 0.022). Although various studies have presented the predictive role of pro-BNP among patients with respiratory distress in the past years, our study did not find BNP to be an accurate predictive and prognostic factor among patients with COVID-19 in our study population. Renal impairment and high Acute Physiology and Chronic Health Evaluation (APACHE) II scores on admission, on the other hand, have demonstrated to be strong predictors for COVID-19 morbidity and mortality. This study could represent an introduction to more prominent multicenter studies to evaluate additional prognostic factors and minimize the ordering of nonspecific testing.